Development of graphite-polymer composites as electrode materials - Calixto,Carolina Maria Fioramonti (2007)
Graphite powder was mixed to polyurethane, silicon rubber and Araldite® (epoxy) in order to prepare composite materials to be used in the preparation of electrodes. Results showed that voltammetric response could be obtained when at least 50% of graphite (w.w-1) is present in the material. SEM and thermogravimetry were also used in the characterization of the composites.